1992
DOI: 10.1021/ie00012a021
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis/gasification of wood in a pressurized fluidized bed reactor

Abstract: The paper deals with pyrolysis and steam gasification of wood in a pressurized fluidized bed reactor. The objective is to study the effect of the treatment conditions on the yield and the reactivity of char. The work shows that in the studied range of the experimental conditions the yield of char is influenced by neither the treatment temperature nor the pressure (650-710 "C and 0.34-1.0 ma). The principal interest is focused on the reactivity of the char in the reaction with steam. It is shown that prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Biomass gasification has been the focus of research in recent years to estimate efficiency and performance of the gasification process using various types of biomass such as sugarcane residue [3], rice hulls [4], pine sawdust [5], almond shells [6], almond [7], wheat straw [8], and food waste [9]. However, only a handful of peer-reviewed journal articles are available on woody biomass gasification [10][11][12][13]. Recently, there has been significant research interest in cogasification of various biomass and coal mixtures such as Japanese cedar wood and coal [14] coal and saw dust [15], coal and pine chips [16], coal and silver birch wood [17], coal, pine, and polyethylene [18], and coal and birch wood [19].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass gasification has been the focus of research in recent years to estimate efficiency and performance of the gasification process using various types of biomass such as sugarcane residue [3], rice hulls [4], pine sawdust [5], almond shells [6], almond [7], wheat straw [8], and food waste [9]. However, only a handful of peer-reviewed journal articles are available on woody biomass gasification [10][11][12][13]. Recently, there has been significant research interest in cogasification of various biomass and coal mixtures such as Japanese cedar wood and coal [14] coal and saw dust [15], coal and pine chips [16], coal and silver birch wood [17], coal, pine, and polyethylene [18], and coal and birch wood [19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some groups (Sjostrom et al, 1994;Kurkela et al, 1994;Madsen and Christensen, 1994;Reinoso et al, 1994;Brage et al, 1995;Chen et al, 1995;de Jong et al, 1998;Collot et al, 1999;Sjostrum et al, 1999;Brown et al, 2000;Pan et al, 2000;Xie et al, 2001;Chmielniak and Sciazko, 2003;McLendon et al, 2004) have reported co-gasification of biomass and coal. Co-gasification brings environmental benefits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass gasification has been the focus of research in recent years to estimate efficiency and performance of the gasification process using various types of biomass such as sugarcane residue (Gabra et al, 2001), rice hulls (Boateng et al, 1992), pine sawdust (Lv et al, 2004), almond shells (Rapagnà and Latif, 1997;Rapagnà et al,2000), wheat straw (Ergudenler and Ghaly, 1993), food waste (Ko et al, 2001), and wood biomass (Pakdel and Roy, 1991;Bhattacharya et al, 1999;Chen et al, 1992;Hanaoka et al, 2005). Recently, co-gasification of various biomass and coal mixtures has attracted a great deal of interest from the scientific community.…”
Section: Biomassmentioning
confidence: 99%